Sod/Livestock-Based Peanut/Cotton Production System: Why We Recommend It! - Tawainga W. Katsvairo; David L. Wright; James J. Marois; D. Hartzog; P. J. Wiatrak; Jimmy R. Rich (EDIS)
SS-AGR-126, a 4-page fact sheet by T. W. Katsvairo, D. L. Wright, J. J. Marois, D. Hartzog, P. J. Wiatrak and J. R. Rich, recommends a four year sod-based rotation system in place of the traditional two year peanut/cotton rotation. Includes a conceptual model of benefits accruing from integrated livestock peanut/cotton farming systems and their interactions. Published by the UF Department of Agronomy, July 2006.